2010
DOI: 10.1177/0961203310370050
|View full text |Cite
|
Sign up to set email alerts
|

Lupus organ damage: what is damaged in Asian patients?

Abstract: Assessment of organ damage has become the standard outcome measure for morbidity and mortality in patients with lupus. Ethnicity is thought to be a marker for genetic, environmental, behavioral, and other variables that may affect disease outcomes. Previous studies suggest that Asians residing in western countries had significantly higher prevalence of damage compared with Whites. In contrast, studies performed in Chinese, Korean and Arab patients showed that the overall prevalence of damage and the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
(94 reference statements)
1
21
1
Order By: Relevance
“…Many studies have reported a younger age at onset of disease in Asian patients, which may allow for greater accumulation of disease‐related damage by a given age. Although overall damage accrual appears otherwise comparable between studies of Asian and Caucasian populations, renal damage is reported to appear excessively in Asians . Additionally, in studies from countries with universal access to healthcare, overall damage and mortality appears to be comparable between Asians and Caucasians, although specific domains of damage, such as renal damage, may be overrepresented in Asian patients in some studies .…”
Section: Damage and Mortalitymentioning
confidence: 86%
See 1 more Smart Citation
“…Many studies have reported a younger age at onset of disease in Asian patients, which may allow for greater accumulation of disease‐related damage by a given age. Although overall damage accrual appears otherwise comparable between studies of Asian and Caucasian populations, renal damage is reported to appear excessively in Asians . Additionally, in studies from countries with universal access to healthcare, overall damage and mortality appears to be comparable between Asians and Caucasians, although specific domains of damage, such as renal damage, may be overrepresented in Asian patients in some studies .…”
Section: Damage and Mortalitymentioning
confidence: 86%
“…Although overall damage accrual appears otherwise comparable between studies of Asian and Caucasian populations, renal damage is reported to appear excessively in Asians. 29 Additionally, in studies from countries with universal access to healthcare, overall damage and mortality appears to be comparable between Asians and Caucasians, although specific domains of damage, such as renal damage, may be overrepresented in Asian patients in some studies. 27,30 In contrast, the most recent 5-year survival rates for SLE in developed Asian countries such as Hong Kong 31 were highly comparable with results from Western centres.…”
Section: Damage and Mortalitymentioning
confidence: 99%
“…Despite these differences, more recent evidence has suggested that Asian patients in the modern era may not necessarily have worse outcomes as traditionally thought. Regardless of varying disease manifestations and severity, the overall rate of damage accrual (as a consequence of disease or due to treatment) in Asian lupus does not seem to be notably different in comparison to Caucasian patients . Moreover, a recent large Medicaid study from the United States even reported lower mortality rates among Asian patients in comparison to their African American, Caucasian and Native American counterparts .…”
Section: Introductionmentioning
confidence: 96%
“…Regardless of varying disease manifestations and severity, the overall rate of damage accrual (as a consequence of disease or due to treatment) in Asian lupus does not seem to be notably different in comparison to Caucasian patients. 9 Moreover, a recent large Medicaid study from the United States even reported lower mortality rates among Asian patients in comparison to their African American, Caucasian and Native American counterparts. 10 A systemic review of SLE patients in China between 1995 and 2013 demonstrated 5-year and 10-year survival rates of 94% and 89%, respectively, which is at least comparable to Western counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies looking at the prevalence of renal damage in patients with SLE among Asians residing in western countries demonstrated a higher prevalence of damage compared to white patients, which was not confirmed in studies performed in China or Korea, but the increased renal damage in Asian patients was almost uniformly reported [49]. Asian patients may also have a higher rate of LN-associated antibodies, LN and more active glomerulonephritis compared to white patients [50].…”
Section: Ethnicity and Outcome Of Sle And Lnmentioning
confidence: 99%